Exploring Mentoring as a Tool for Career Advancement of Academics in Private Higher Education Institutions in Malaysia - Ismail, Maimunah; Lawrence, Arokiasamy (The Journal of International Social Research, 2007)
Mentoring refers to a dyadic relationship between a more experienced member of an organization with a less experienced individual. Mentoring provides support as a mentor acts as a role model. Mentoring is important for organizational development as it implies workplace learning and leadership principles in career advancement. The functions of a mentor are to teach, coach, support and guide a protégé, to progress in his/her career. This article theoretically explores the roles of mentoring in career advancement of academics in private higher education institutions.